Endosomal pH, Redox Dual-Sensitive Prodrug Micelles Based on Hyaluronic Acid for Intracellular Camptothecin Delivery and Active Tumor Targeting in Cancer Therapy - Huiping Zhang; Liang Li; Wei Li; Hongxia Yin; Huiyun Wang; Xue Ke (MDPI AG, 2024)
Background: CPT is a pentacyclic monoterpene alkaloid with a wide spectrum of antitumor activity. Its clinical application is restricted due to poor water solubility, instability, and high toxicity. We developed a new kind of multifunctional micelles to improve its solubility, reduce the side effecs, and obtain enhanced antitumor effects. Methods: We constructed HA-CPT nano-self-assembly prodrug micelles, which combined the advantages of pH-sensitivity, redox-sensitivity, and active targeting ability to CD44 receptor-overexpressing cancer cells. To synthesize dual sensitive HA-CPT conjugates, CPT was conjugated with HA by pH-sensitive histidine (His) and redox-sensitive 3,3'-dithiodipropionic acid (DTPA). In vitro, we studied the cellular uptake and antitumor effect for tumor cell lines. In vivo, we explored the bio-distribution and antitumor effects of the micelles in HCT 116 tumor bearing nude mice. Results: The dual-sensitive and active targeting HA-His-ss-CPT micelles was proved to be highly efficient in CPT delivery by the in vitro cellular uptake study. The HA-His-ss-CPT micelles escaped from endosomes of tumor cells within 4 h after cellular uptake due to the proton sponge effect of the conjugating His and then quickly released CPT in the cytosol by glutathione (GSH). In mice, HA-His-ss-CPT micelles displayed efficient tumor accumulation and conspicuous inhibition of tumor growth. Conclusions: The novel, dual-sensitive, active targeting nano-prodrug micelles exhibited high efficiency in drug delivery and cancer therapy. This "all in one" drug delivery system can be realized in an ingenious structure and avoid intricate synthesis. This construction strategy can illume the design of nanocarriers responding to endogenous stimuli in tumors.